Innovative adoption model for digital health technologies among elderly with chronic diseases: Integrating Unified Theory of Acceptance and Use of Technology and Knowledge-Attitude-Practice model in a survey of 1222 patients in Shanghai - Chen, Y.; Yuan, J.; Li, C.; Wang, H.; Shi, L.; Zhao, S.; Oliveira, A.; Zhao, L. (BMJ Open, 2026)
Objective To propose and test an innovative model by integrating the Unified Theory of Acceptance and Use of Technology and Knowledge-Attitude-Practice model to explain the mechanisms influencing the adoption of digital health technologies by elderly patients with chronic diseases from the perspective of both internal and external factors, promoting the acceptance and utilisation of digital health technologies among elderly chronically ill patients. Study design A face-to-face questionnaire survey was conducted from July to September 2023. Study setting The study was conducted in 12 medical institutions in Shanghai, including 6 tertiary hospitals, 3 secondary hospitals and 3 community hospitals. Participants 1222 participants aged 60 years or more, diagnosed with one or more of the following chronic diseases: essential hypertension, type 2 diabetes, coronary atherosclerotic heart disease, stroke and chronic obstructive pulmonary disease, were involved in the study using convenience sampling. Critically ill emergency patients and those who were involved in medical disputes were excluded. Outcome measure The behavioural intention and usage behaviour of older patients with chronic diseases to use digital health technologies. Results The explanatory power of the proposed model for behavioural intention was 72.9%. There is a significant negative association between technology anxiety and the intention to use digital health technologies among older patients with chronic diseases (?=−0.224, p<0.001); effort expectancy (?=0.530, p<0.001) and performance expectancy (?=0.193, p<0.001) were also significantly associated with intention to use digital health technologies. Men (?=−0.104, p=0.016), relatively younger (?=−0.061, p=0.005), with experience in using digital health technologies (?=−0.452, p<0.001) were more likely to translate behavioural intention into use behaviour. Conclusions Acceptance of digital health technologies among older patients with chronic diseases was associated with a combination of internal and external factors, with the former playing a dominant role. These valuable findings provided insights and inspiration for improving digital health technologies acceptance and utilisation among older patients with chronic diseases.